Promoter Methylation Status of Breast Cancer Susceptibility Gene 1 and 17 Beta Hydroxysteroid Dehydrogenase Type 1 Gene in Sporadic Breast Cancer Patients - Marwa M. Hosny; Nagwan A. Sabek; Taghrid B. El-Abaseri; Fathalla M. Hassan; Sherif H. Farrag (International Journal of Breast Cancer)
Epigenetic modifications are involved in breast carcinogenesis. Identifying genes that are epigenetically silenced via methylation could select target patients for diagnostic as well as therapeutic potential. We assessed promoter methylation of breast cancer susceptibility gene 1 (BRCA1) and 17 Beta Hydroxysteroid Dehydrogenase Type 1 (17βHSD-1) in normal and cancer breast tissues of forty sporadic breast cancer (BC) cases using restriction enzyme based methylation-specific PCR (REMS-PCR). In cancerous tissues, BRCA1 and 17βHSD-1 were methylated in 42.5% and 97.5%, respectively, while normal tissues had 35% and 95% methylation, respectively. BRCA1 methylation in normal tissues was 12.2-fold more likely to associate with methylation in cancer tissues (p<0.001). It correlated significantly with increased age at menopause, mitosis, the negative status of Her2, and the molecular subtype “luminal A” (p=0.048, p=0.042, p=0.007, and p=0.049, resp.). Methylation of BRCA1 and 17βHSD-1 related to luminal A subtype of breast cancer. Since a small proportion of normal breast epithelial cells had BRCA1 methylation, our preliminary findings suggest that methylation of BRCA1 may be involved in breast tumors initiation and progression; therefore, it could be used as a biomarker for the early detection of sporadic breast cancer. Methylation of 17βHSD-1 in normal and cancer tissue could save patients the long term use of adjuvant antiestrogen therapies.